Administração de cloreto de mercúrio a ratas em desenvolvimento : efeitos sobre o tecido ósseo de ratas adultas de diferentes idades - Bezerra, Juciléia Barbosa (2009)
The bone tissue is influenced by internal and external factors and heavy metals, as mercury, are examples of external or environmental factors. The mercury chloride (HgCl2) when absorbed by human body, deposits in the bone and fat tissue and dislocates bones and muscles minerals to circulation, being able to provoke illnesses. In this study, Wistar rats were divided in 4 groups: 3m, 6m, 9m and 12 months (12m) days of life. The animals were treated with HgCl2 or saline through gavage. The treatment began at 30 days of age, 5 times per week, during 60 days. The daily dose was of 0,3mg/Kg of body weight (BW) of HgCl2 and 0,1ml of saline/100g BW. After this period, the group 3m was sacrificed immediately afterwards by decapitation whereas the other groups had remained without treatment until they completed the desired age. The right femurs and vertebrae (L5) were removed for biometrics, physical and biomechanics analysis. The treatment with mercury chloride induced higher values of physical and biometric parameters in the 6m group and lower values in the 12m group and no odifications in the 3 and 9 m groups, when compared with saline treatment. Moreover, the treatment with CM promoted rats vaginal opening with 51 days of life in treated group whereas in the controls this opening occurred in 44,4 days of life.We concluded that the treatment with HgCl2, in the dose of 0,3mg/Kg BW retarded the age at the speed change of the growth of the animals, especially in 6m and 12m groups. Moreover, the HgCl2 promoted bone fragility in animals from 12m group, as can be observed by the analysis of the biometrics, physicals and biomechanics properties, in both femur and vertebrae. The treatment with CM still delayed the sexual maturity of rats.